Efficacy of 177Lu- and 90Y-labeled nanoparticles in targeted tumor therapy in a mouse CT26 and 4T1 xenograft model - Stanković, Dragana; Janković, Drina; Mirković, Marija; Radović, Magdalena; Milanović, Zorana; Vukadinović, Aleksandar; Stanković, Aljoša; Perić, Marko; Vranješ-Djurić, Sanja; Prijović, Željko; Savić, Miroslav (Archives of Pharmacy, 2022)
Nanoparticle delivery to solid tumors after an intravenous injection has shown to be very limited in its ability to achieve therapeutic dosage in the tumor due to nonspecific nanoparticle uptake by RES. To overcome these problems, local intratumoral injection of nanoparticles is being investigated as more relevant route of administration. In the present study, superparamagnetic iron oxide nanoparticles (SPIONs) were synthetized, coated with citric (CA) or dimercaptosuccinic acid (DMSA) and radiolabeled with 90Y or 177Lu, aiming to develop radioactive nanoparticles for localized tumor therapy.  Biodistribution and antitumor efficacy of radiolabeled SPIONs after local intratumoral administration in CT26 or 4T1 xenografts-bearing BALB/c mice were studied. Tracking the radioactivity distribution of injected 90Y-CA-SPIONs and 177Lu-DMSA-SPIONs revealed that due to the size of the nanoparticles, their diffusive escape from the tumor into healthy organs and tissues is slowed down; the particles remain at the injection site up to 14 days after the injection, and thereby increasing the tumor's exposure to radiation. Lower therapeutic efficacy of 177Lu-DMSA-SPIONs in CT26 or 4T1 tumor can be explained by slight diffusion of particles from injection sites into distant tumor regions and moderate-energy β-particles emitted by 177Lu (0.5MeV). These studies suggest that 90Y-CA-SPIONs is superior to 177Lu-DMSA-SPIONs at inhibiting both tumors growth, due to the high-energy β-particles emitted by 90Y (2.27MeV) and a longer path length.90Y is therapeutically superior to 177Lu in investigated xenograft models. We believe that an intratumorally injected radiolabeled SPIONs can be considered as a potential therapeutic agent for localized cancer therapy.